Validità concorrente e predittiva del Test di Orientamento Motivazionale Versione generale (TOM-VG) - Alessandri, G.; Dello Russo, S. (Giornale Italiano di Psicologia, 2011)
The present study investigates the extent to which the four dimensions of TOM-VG (goal, leadership, innovation and relation orientation) predict job performance, over and above personality traits. Findings attest to the positive significant correlation between leadership, goal and relation orientation with job performance. Logistic regression attest to the loss of predictive power of goal orientation when variance accounted for by personality traits was ruled out, whereas the regression of leadership and relation orientation remained still significant, over and above the significant proportion of variance accounted for by personality traits.